DEVELOPMENT OF GUGGULSTERONE-LOADED PHYTOSOMES: A QUALITY BY DESIGN-BASED CHARACTERIZATION AND OPTIMIZATION STUDIES - DUDEKULA, JAMAL BASHA; KOILPILLAI, JEBASTIN; NARAYANASAMY, DAMODHARAN (International Journal of Applied Pharmaceutics, 2024)
Objective: The primary objective of this study was to enhance drug delivery efficiency through the design and optimization of guggulsterone-pyrosomes, employing a 3-factor, 3-level box-behnken design. Methods: The methodology involved a solvent evaporation technique utilizing guggulsterone and soy lecithin, with a systematic variation and optimization of critical factors such as soy lecithin and guggulsterone concentration, alongside temperature adjustments to refine the phytosome formulations. The characterizations of these formulations were extensive, with a particular emphasis on key quality attributes, notably percentage entrapment efficacy and drug release. Results: The optimized guggulsterone-pyrosomes demonstrated impressive outcomes, showcasing a remarkable entrapment efficiency of 92.64% and a noteworthy drug release rate of 91.69% at 24 h. These formulations displayed heightened viability in selected cell lines, exhibiting cellular toxic c concentrations ranging from 253.39 to 330.44 µg/ml. Moreover, they exhibited stability under stressed conditions from a physicochemical perspective. The particle size was measured at 137.8 nm, with a zeta potential of-25.3 mV. Conclusion: Significantly, the extended drug release from guggulsterone-pyrosomes adhered to first-order kinetics with Fickian diffusion. In summary, this study underscores the efficacy of the box-behnken design in crafting optimized guggulsterone-pyrosomes, showcasing their potential as promising drug delivery carriers. The enhanced drug delivery platform exhibits significant promise in amplifying antihyperlipidemic effects, attributed to the improved performance and stability of these innovative phytosomes